Farms, cooperatives and plots on the Peruvian coast 1968-1986: the state of affairs - Portocarrero Maish, Javier (Universidad del Pacífico, 1987)
​In the last two decades the development, of agriculture in Peru has attracted an increasing interest within the social sciences. In particular, the process of transformation of the 'haciendas' (farms) into cooperative associations in the Peruvian coast, and the subsequent parceling of the latter, has produced an extensive bibliography on the subject. A balance sheet of this intelectual production is the main object of this paper. Starting with the collection of these works, the author seeks to provide some elements with which to answer the following questions, amongst others: What should be done with those cooperative associations which still exist? Should the process of "parcelación" be checked, or even reversed, promoting new forms of associatlon instead? What are the bottlenecks of parcelized production, and how should they be faced? Is a re-concentratton of lands to be expected in the long run? Finally, can it be avoided without a loss of efficiency?